1993
DOI: 10.1159/000238971
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Resistance of <i>Streptococcus pneumoniae </i>to Quinolones in vitro

Abstract: Twelve strains of Streptococcus pneumoniae were serially exposed to increasing concentrations of levofloxacin, temafloxacin, ciprofloxacin and norfloxacin for five passages. Wild-type and passaged strains were tested for susceptibility to quinolones, macrolide and penicillin G. The MIC90 data showed a 2-fold increase for levofloxacin but a 32-fold increase for ciprofloxacin, a 16-fold increase for temafloxacin and an 8-fold increase for norfloxacin. Among 16 ciprofloxacin-induced resistant strains, 14 were sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…In this study we showed, on July 10, 2020 by guest http://aac.asm.org/ evaluation period in this study, the condition does not simulate actual human pharmacokinetics when dosing q12h is utilized in patients with normal renal function. In this study, the development of resistance to ciprofloxacin for all study isolates was apparent, especially after 24 h. The induction of resistance of S. pneumoniae to FQ in vitro has been previously reported (19). After repeated transfer in ciprofloxacin, temafloxacin, and norfloxacin there was an 8-to 16-fold decrease in susceptibility, while after transfer in levofloxacin only minimal decreases in susceptibility were observed.…”
Section: Discussionsupporting
confidence: 77%
“…In this study we showed, on July 10, 2020 by guest http://aac.asm.org/ evaluation period in this study, the condition does not simulate actual human pharmacokinetics when dosing q12h is utilized in patients with normal renal function. In this study, the development of resistance to ciprofloxacin for all study isolates was apparent, especially after 24 h. The induction of resistance of S. pneumoniae to FQ in vitro has been previously reported (19). After repeated transfer in ciprofloxacin, temafloxacin, and norfloxacin there was an 8-to 16-fold decrease in susceptibility, while after transfer in levofloxacin only minimal decreases in susceptibility were observed.…”
Section: Discussionsupporting
confidence: 77%
“…Ciprofloxacin-resistant strains of S. pneumoniae have been reported, and most troubling is the possibility of cross-resistance to the newer fluoroquinolones (11,21,26,27,32). These compounds have improved activity against topoisomerase IV, which is thought to be the primary target for most fluoroquinolones in gram-positive organisms such as S. pneumoniae and Staphylococcus aureus.…”
mentioning
confidence: 99%
“…However, 0.5% of S. pneumoniae in France are resistant to sparfloxacin (MIC>4 μg/ml) and other fluoroquinolones (3, 4. The selection of S. pneumoniae resistant to quinolones has also been demonstrated in vitro (5). We report herein the in vivo selection of a strain of S. pneumoniae resistant to fluoroquinolones, including sparfloxacin.…”
mentioning
confidence: 99%